Influence of ultrasound treatment and dynamic (in-situ) ultrasound loading on the temperature hysteresis of electrophysical characteristics in irradiated n-Si–Fz - Babych, V.М.; Olikh, Ja.М.; Tymochko, M.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Presented in this paper are experimental results of ultrasound treatment (UST) and dynamic ultrasound loading (USL) influences on the electric activity of radiation defects (after y-irradiation) in crystals n-Si–Fz. The results are obtained using the Hall effect method within the temperature range 100–300 K. Peculiarities of US action in the treatment and loading modes on the temperature hysteresis of electrophysical characteristics in investigated material (extension and narrowing) were analyzed. Diffusion and deformation mechanisms responsible for US modification of defect complexes have been suggested.